Analysis of the pseudogap-related structure in tunnel spectra of the superconducting Bi₂Sr₂CaCu₂O₈₊δ revealed by break-junction technique - Ekino, T.; Gabovich, A.M.; Voitenko, A.I. (Физика низких температур, 2008)
Tunnel conductance G(V)for break-junctions made of as-grown single-crystal Bi₂Sr₂CaCu₂O₈₊δ samples with Tc≈86-89 K was measured and clear-cut dip-hump structures (DHSs) were found in the range 80-120mV of the bias voltage V. The theory of tunneling in symmetric junctions between inhomogeneous charge-density-wave (CDW) superconductors, considered in the framework of the s-pairing model, has been developed. CDWs have been shown to be responsible for the appearance of the DHS in the tunnel current- voltage characteristics and properly describes experimental results.